Factors influencing normalisation and sustainment of the Birmingham Symptom-specific Obstetric Triage System (BSOTS): a qualitative implementation evaluation study with UK maternity health professionals - Nimarta Dharni; Agnieszka Latuszynska; Sophie-Anna Dann; Nina Johns; Graeme Currie; Sara Kenyon (Implementation Science Communications)
Abstract Background Maternity triage is the emergency portal to access maternity services for pregnant or newly postnatal women experiencing unexpected complications or concerns. Traditionally women were seen in the order in which they attended maternity services without appropriate organisational and clinical systems in place to prioritise the clinical urgency of the women presenting. The Birmingham Symptom-specific Obstetric Triage System (BSOTS) is a standardised triage system co-developed by clinicians and researchers to address this need. Since its inception in 2013, BSOTS is now the recommended triage system and has been widely implemented in the UK with international adoption also occurring. This study aimed to explore the factors influencing the normalisation and sustainment of BSOTS in UK maternity units. Methods A qualitative evaluation study involving semi-structured interviews with 43 maternity professionals across 9 sites representing a range of implementation experiences (normalised n=3, partially normalised n=3, and probably not normalised n= 3). Participants were maternity triage staff of varying levels including midwives, obstetricians and senior leaders. Interviews were held virtually, and recorded and transcribed verbatim. Analysis was based on Normalisation Process Theory. Results Contextual factors were key to influencing implementation and sustainment of BSOTS. In sites where BSOTS was normalised and integrated into routine practice, organisational and leadership buy-in helped mobilise support for other contextual factors required for implementation fidelity and success, including establishing a clear identity of the triage department, sufficient midwifery and obstetric staffing, appropriate space, a dedicated and protected core team, adequate equipment and resources. Accommodating these factors often meant complex system-level changes were required to implement BSOTS for which strategic intentions and organisational support were integral. In some cases, such support was facilitated by Care Quality Commission regulatory recommendations. Conclusions Our study found successful implementation and normalisation of BSOTS was driven by contextual factors, particularly organisational buy-in and leadership support. While regulatory requirements enabled the prioritisation of triage within maternity services, our evaluation emphasised the importance of both leadership and frontline staff support for effective integration and sustainment. Evaluation findings were used to inform an implementation toolkit for clinical triage teams seeking to implement or reinvigorate BSOTS in their sites.